Luck of the draw - Daniels, B. J (Daniels, B. J. Sterling's Montana., 2019)
When Garrett Sterling leaves for a horseback ride through his family<U+2019>s sprawling Montana property, he<U+2019>s expecting a relaxing break from the construction at the Sterling guest ranch. What he gets is something far more sinister. It all happens so fast that it<U+2019>s hard for Garrett<U+2014>and the authorities<U+2014>to sort out the facts. Two things are certain, though: someone is dead and the killer knows there was a witness. But when the one woman he could never forget emerges as a key suspect in the investigation, Garrett will do anything he can to help clear her name. She<U+2019>s still keeping secrets from him<U+2014>that much is clear. But Garrett won<U+2019>t rest until he uncovers what really happened that day, how she<U+2019>s involved<U+2014>and why everything she<U+2019>s ever told him is a lie.